Pengembangan Material Komposit Keramik Berpori dari Bahan Clay yang diperkuat Bahan Kuningan dengan Menggunakan Metode Ekstrusi - Muh Amin; Muhammad Subri (Universitas Muhammadiyah Semarang, 2017)
Successful porcelain ceramic composite material made from Clay, TiO2 and Activated Carbon is reinforced by Brass. As a foaming agent used Polyvinyl Alcohol. The material made by using this extrusion method can produce porous ceramic material with porosity equal to 78,74% with density equal to 4,42 gram / cm3. The results were also reinforced by XRD and SEM testing.Keywords: Porous Ceramics, Composites, Extrusions, CuZn, Clay.